Control Schemes for Disturbance Rejection: A Case Study - Figueroa, Jose Luis (2001)
Chemical processes are usually designed to work under a specified set of conditions; therefore the first goal of a regulatory control scheme is to keep the controlled variable at or near these conditions in the presence of disturbance and model uncertainty.  In this paper, we present some control schemes to deal with some special problems of disturbance rejection.  The usefulness of these alternatives is discussed within the context of controlling a simple flowsheet example.